2022
DOI: 10.1002/cbin.11888
|View full text |Cite
|
Sign up to set email alerts
|

Cancer in Amphibia, a rare phenomenon?

Abstract: Compared to other animals, the spontaneous occurrence of tumors in wild amphibians is relatively rare, generally limited to specific populations or species.The number of reports of spontaneous tumors in amphibians known up to 1986 was 491 cases in anurans and about 253 cases in urodeles. Similarly, there have been many, unsuccessful attempts to chemically or biologically induce tumors in amphibians. With these considerations, it is inevitable to wonder: do urodeles and anurans have an inherent resistance to ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
0
1
0
Order By: Relevance
“…In this work, we have established the novel findings that squamates and amphibians both have a positive relationship between body mass and neoplasia prevalence, and amphibians also have a positive relationship between body mass, lifespan, and cancer. It has been proposed that regenerative capacities, as observed in some amphibian species, may be associated with tumor suppression mechanisms 28,29 , and that regeneration in amphibians, unlike mammals, does not necessarily result in increased cancer prevalence 30,31 . This hypothesis needs further exploration since we found that amphibians had lower neoplasia and cancer prevalence than mammals and squamates, but higher than birds.…”
Section: Discussionmentioning
confidence: 99%
“…In this work, we have established the novel findings that squamates and amphibians both have a positive relationship between body mass and neoplasia prevalence, and amphibians also have a positive relationship between body mass, lifespan, and cancer. It has been proposed that regenerative capacities, as observed in some amphibian species, may be associated with tumor suppression mechanisms 28,29 , and that regeneration in amphibians, unlike mammals, does not necessarily result in increased cancer prevalence 30,31 . This hypothesis needs further exploration since we found that amphibians had lower neoplasia and cancer prevalence than mammals and squamates, but higher than birds.…”
Section: Discussionmentioning
confidence: 99%
“…Due to their natural resistance to cancer, spontaneous tumors in amphibians are rare, and even in laboratory settings, it is challenging to induce tumors using chemical or biological methods. This natural advantage makes amphibians a promising source for mining anticancer substances [ 134 ]. With the advent of new technologies and methods to enhance drug efficacy and promote drug development and clinical transformation, it is expected that more highly effective anticancer substances will be discovered and elucidated.…”
Section: Prospects For the Development Of Natural Anticancer Peptides...mentioning
confidence: 99%